1999
DOI: 10.1002/j.2161-1882.1999.tb00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Research: Korean International Students' Expectations About Counseling

Abstract: 990) reported that 50 % of Asian Americans tend to terminate counseling after the first interview, in contrast to a 30% termination rate for Caucasian American clients. The authors attributed this phenomenon to a lack of understanding between the majority therapist and the minority client regarding each other and the counseling process. Leong (I 986) suggested that there are many cultural factors influencing Asian Americans' receptiveness to counseling and psychotherapy. He reported that Asian American client… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 12 publications
(10 reference statements)
2
20
3
1
Order By: Relevance
“…These findings contradict previous research that suggested that international students underutilize services or are more pathologized than U.S. students (Byon et al, 1999;Nilsson et al, 2004). The results suggest that assessing nonclient samples may say little about how students will use services.…”
Section: Clinical and Programmatic Implications For Counseling Centerscontrasting
confidence: 96%
See 1 more Smart Citation
“…These findings contradict previous research that suggested that international students underutilize services or are more pathologized than U.S. students (Byon et al, 1999;Nilsson et al, 2004). The results suggest that assessing nonclient samples may say little about how students will use services.…”
Section: Clinical and Programmatic Implications For Counseling Centerscontrasting
confidence: 96%
“…Both U.S. and international students tended to have the same top presenting concerns, most frequent diagnoses, GPA, living situation, sexual orientation, previous on-campus counseling, disposition, referral for on-campus psychiatric evaluation, premature termination rates, and mean number of sessions attended. These findings contradict previous research that suggested that international students underutilize services or are more pathologized than U.S. students (Byon et al, 1999;Nilsson et al, 2004). The results suggest that assessing nonclient samples may say little about how students will use services.…”
Section: Clinical and Programmatic Implications For Counseling Centerscontrasting
confidence: 96%
“…This is consistent with related work (e.g. Nilsson et al 2004;Singaravelu et al 2005) which has previously identified international students as not engaging with careers services due to differences in cultural values (Byon et al 1999) or their support not to be seen as worthwhile (Shen and Herr 2004). Chinese students may present a specific challenge for careers services to engage with as traditionally family influence exerts an impacts on Asian students' career choices (Sun 2015;Wong and Liu 2010;Yi et al 2003;Yoo and Skovholt 2001), though this may not hold true from the data we presented above.…”
Section: University Support To Develop Future Employabilitysupporting
confidence: 90%
“…Byon, Chan, and Thomas (1999) used cluster analysis to distinguish the responses of 136 Korean international students on a translated version of the EAC-B. Though the authors did not explicitly define the three groups that emerged from their analysis, readers can make some inferences about these groups by examining the statistical table that showed how the three groups differed on the 17 scales of the EAC-B.…”
mentioning
confidence: 99%